Job lock: Evidence from a regression discontinuity design - Robert W. Fairlie; Kanika Kapur; Susan Gates (University College Dublin, UCD School of Economics, 2012)
Employer-provided health insurance in the United States is suspected of restricting job mobility, resulting in job lock. Previous research on job lock finds mixed results using several methodologies. We take a new approach to examine whether employer-based health insurance discourages job mobility by exploiting the discontinuity created at age 65 through the qualification for Medicare. Using a novel procedure for identifying age in months from matched monthly CPS data and a relatively unexplored administration measure of job mobility, we compare job mobility among male workers in the months just prior to turning age 65 to job mobility in the months just after turning age 65. We find no evidence that job mobility increases at the age 65 threshold when Medicare eligibility starts. Our results are robust to different bandwidths, non-linear age profiles, and frequency of age measurement. The upper bounds of 95 percent confidence intervals for these estimates can rule out the existence of any job lock in some cases, and in most cases can rule out the large levels of job lock found in many previous studies in the literature. We also do not find evidence that other factors such as retirement, reduction in hours worked, social security eligibility, pension eligibility, and sample changes confound the results on job mobility in the month individuals turn 65.
Keywords: J60; I13; 330; Job lock; health insurance; Medicare